Isolation of Piperine compound from Black Pepper Seeds and Synthesis of it some new derivatives - Ebraheem, HibaA. (Al-Qadisiyah Journal of Pure Science, 2017)
An efficient isolation of Piperine(1) from the black Pepper seed ethanolic extract was reported . the pure isolated piperine was reacted with urea thiourea ,hydrazine , phenyl hydrazine ,and hydroxyl amine hydrochloride to give pyrimidinone , pyrimidinethione pyrazolin, phenylpyrazolin and oxime derivatives (2a-2g). All the reported compounds were confirmed by the available physical and spectral methods.